Analisis Kepuasan Pelanggan Menggunakan Model Kano Dimensi SERVQUAL dan CSI Terhadap Layanan Sertifikat Tanah Di BPN (Badan Pertanahan Nasional) - Juwita Artanti Kusumaningtyas; Eko Sediyono (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2017)
BPN (National Land Agency) Salatiga is a government institution that serves in the land sector of national, regional, and sectoral according to the legislation. The purpose of this study is to measure the quality of service BPN to determine customer satisfaction by using the Kano model of SERVQUAL dimensions and CSI. The data collection is done with the distribution of questionnaires to the public and conduct interviews of the BPN. The results showed BPN customer satisfaction is the percentage of 78%. The results showed Borderline or on the boundary quite satisfied and need to maximize customer service BPN Salatiga.